2018
DOI: 10.7150/jca.22841
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smoking and XPG, CYP1A1, OGG1, ERCC5, ERCC1, MMP2, and MMP9 Gene Polymorphisms with the early detection and occurrence of Laryngeal Squamous Carcinoma

Abstract: A total of 200 smoking-related laryngeal carcinoma patients with pathology confirmation from the Eye and ENT Hospital and 190 high-risk smokers were included in a survey. All of the participants had a smoking index greater than 400 (cigarettes/day*year.) We obtained data on clinical and baseline characteristics, and peripheral blood was obtained and subjected to DNA extraction to analyse the correlation between smoking and the occurrence of laryngeal carcinoma. We selected candidate genes and SNP fragments tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
12
1
1
Order By: Relevance
“…Matrix metalloproteinases (MMPs) are a family of zinc-dependent endopeptidases which are involved in multiple biological functions. Among MMPs, MMP2 and MMP9 were recognized as the key factors of cell migration in tumors 26-28. In this study, we found that the expression of MMP2 and MMP2 decreased on a dose dependent manner by recombinant GSN stimulation, which indicated that the secreted GSN could restrain the invasion and migration ability of colon cancer cells by decreasing the levels of MMP2 and MMP9.…”
Section: Discussionmentioning
confidence: 62%
“…Matrix metalloproteinases (MMPs) are a family of zinc-dependent endopeptidases which are involved in multiple biological functions. Among MMPs, MMP2 and MMP9 were recognized as the key factors of cell migration in tumors 26-28. In this study, we found that the expression of MMP2 and MMP2 decreased on a dose dependent manner by recombinant GSN stimulation, which indicated that the secreted GSN could restrain the invasion and migration ability of colon cancer cells by decreasing the levels of MMP2 and MMP9.…”
Section: Discussionmentioning
confidence: 62%
“…A study by Zhu Li et al investigated (SNP) polymorphisms for the genes XPG, CYP1A1, OGG1, ERCC5, ERCC1, MMP2 and MMP9 in a group of 200 patients with larynx cancer associated with heavy smoking in Shanghai (China), finding an association between SNP of genes CYP1A1 and MMP9 and larynx cancer. The authors proposed that these SNPs act as markers of an increased susceptibility to developing larynx cancer among smokers [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that tobacco exposure can reduce the expression of multiple DNA repair genes [50]. However, interestingly, our ANOVA results showed increased protein levels of OGG1 and NEIL2 as well as enhanced transcriptional level of NTH1 in the cells exposed to smoke compared with the non-smoking ones.…”
Section: Discussionmentioning
confidence: 46%
“…ATRA and β-carotene were dissolved in ethanol, while dimethyl sulfoxide (DMSO) was used as a carrier solvent for lycopene; cells were pretreated with these compounds at different doses (1 nM, 10 nM, 100 nM, 1 µM, and 10 µM) for 24 h. Then, lids of the plates were removed to expose lung cancer cells to one cigarette smoke from University of Kentucky research cigarettes (brand 1A1, 25 mg tar, 0.3 mg nicotine, [34]) using the chamber shown in Figure 1. The time-course experiment (10,20,30,40,50 and 60 min) was carried out to determine the optimal duration of exposure, leading to selecting a time point of 50 min, which was published previously [35,36].…”
Section: Cell Culturementioning
confidence: 99%